The Role of Corporate Governance Mecanism in Enhancing Firm Value with CSR as Moderating Variable - Mita, Shelo; Saharah, Siti; Yulianto, Agung (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Within the framework of GCG research, a company's value is an indicator of how well its performance and sustainability are assessed from the viewpoints of investors and shareholders. The study examines how corporate social responsibility disclosure (CSR) and effective corporate governance practices (GCG), including the presence of an audit committee, institutional ownership, and managerial ownership, influence firm value.  Additionally, it explores the moderating effects of these factors on the relationship between CSR, GCG, and firm value. To determine the relationship between variables, this study uses a quantitative approach method where data is collected in the form of numbers and analyzed using the Eviews application. The study encompassed all mining corporations that were publicly listed on the Indonesia Stock Exchange (IDX) between 2020 and 2022. Purposive sampling was used for sampling, and resulted in a research sample of 99 companies. There is no discernible impact on managerial ownership, institutional ownership, and the presence of an audit committee regarding the moderated relationship between CSR and firm value because the probability value of the interaction between IO and CSR 0.9582 > 0.05, AC and CSR 0.8528 > 0.05, and MO and CSR 0.6689 > 0.05 more than 0.05. Thus, hypotheses H4, H5, and H6 which predict that MO, IO, and AC will have an impact on firm value when moderated by CSR are not proven correct based on the test results. The study results validate that institutional and managerial ownership positively impact firm value in a significant manner, whereas the audit committee exerts a positive yet statistically insignificant influence.